Alternative energy 101 introduction to manufacturing fuel cells & advanced batterries - Society of Manufacturing Engineers (Michigan : Society of Manufacturing Engineers, 2004)
A manufacturing primer on alternative energy technologies and fuel cells. Experts in the field provide fundamental information with detailed descriptions of alternative energy. Useful to those wishing to become a supplier to the growing alternative energy industry
Disc 1. Overview of alternative energy technologies / Frank E. Jakob -- Renewable energy 101 / Keith Wipke -- Fundamentals of alternative energy technologies / Levi T. Thompson -- Introduction to fuel cells / Tom A. Zawodzinski. Disc 2. Production scale-up of AMTEC manufacturing processing / Edward F. Mussi -- The advanced stored energy systems dilemma / James S.B. Chew -- Portable solid oxide fuel cells / Aaron Crumm -- Alternative energy 101 questions & answers / Alternative energy speaker panel
Title from title screen
Executive producer, Steven R. Bollinger
Keywords: Renewable energy sources; Power resources; Fuel cells; Solid oxide fuel cells; Energy development